2020
DOI: 10.3389/fphar.2020.585838
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Insulin-Regulated Aminopeptidase (IRAP) Inhibitors: A Literature Review

Abstract: Insulin-Regulated Aminopeptidase (IRAP, EC 3.4.11.3) is a multi-tasking member of the M1 family of zinc aminopeptidases. Among its diverse biological functions, IRAP is a regulator of oxytocin levels during late stages of pregnancy, it affects cellular glucose uptake by trafficking of the glucose transporter type 4 and it mediates antigen crosspresentation by dendritic cells. Accumulating evidence show that pharmacological inhibition of IRAP may hold promise as a valid approach for the treatment of several pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…As an interesting feature of IRAP function, inhibiting IRAP activity has been shown to be a plausible way of enhancing memory [ 13 , 14 ]. To characterize inhibition of the purified IRAP, we select a short peptide inhibitor (VYPWT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an interesting feature of IRAP function, inhibiting IRAP activity has been shown to be a plausible way of enhancing memory [ 13 , 14 ]. To characterize inhibition of the purified IRAP, we select a short peptide inhibitor (VYPWT).…”
Section: Resultsmentioning
confidence: 99%
“…IRAP functions in different locations and pathways from ERAP1 and ERAP2 for MHC-I antigen presentation [ 4 , 6 ]. In addition to its immunological importance, IRAP is also a potential memory enhancing target for cognition improvement [ 13 , 14 ]. For most of the IRAP characterization studies reported so far, the recombinant protein was expressed with relatively low yields using mammalian cells such as HEK or COS7 cells, or insect cells sf9 or sf21 [ 8 , 9 , 15 , 16 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRAP has been shown to be important in cross-presentation [ 266 ] and an IRAP inhibitor to be able to enhance cytotoxic responses ex vivo [ 267 ]. Furthermore, the development of inhibitors for these enzymes has reached significant maturity [ 268 , 269 , 270 ]. However, the synergism between inhibition of intracellular antigen processing by aminopeptidases and enhancement of antitumor immunity by ICI has not been explored yet.…”
Section: Strategies For Enhancing Ici Therapy Effectiveness: Thementioning
confidence: 99%
“…Consequently, it is not surprising that during the last 10–15 years, considerable efforts have been devoted to the discovery of small molecule IRAP inhibitors as potential cognitive enhancers. Comprehensive reviews are now available, and existing IRAP inhibitors reported include drug-like scaffolds like sulfonamides (5) or benzopyrans (6–9, Figure 1 ) ( Hallberg, 2009 ; Barlow and Thompson, 2020 ; Georgiadis et al, 2020 ; Hallberg and Larhed, 2020 ). The later scaffold was identified in 2008 by virtual screening, and subsequently optimized resulting in a series coined as HFI (Howard Florey Institute) ( Albiston et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%